Genetic diversity and temporal dynamics of phytoplankton viruses in East Lake, China - Wang, Mei-Niang (Virol Sin, 2015)
Phytoplankton viruses are important components of aquatic ecosystems. However, their prevalence and genetic diversity in marine and freshwater systems are largely under estimated owing to the immense size of water bodies and limitations in virus discovery techniques. In this study, we conducted a 1-year survey of phytoplankton virus communities by collecting surface water monthly from an inland lake (East Lake) in China between May 2012 and April 2013. We examined four phytoplankton viruses, i.e., myoviruses, podoviruses, siphoviruses, and phycodnaviruses, and seven sets of primers were used to target conserved genes within these four species. In this year-long investigation, a total of 358 different virus-related sequences from four virus families were obtained. All virus families were detected in all months, except for cyanopodoviruses, which were only identified during eight of the 12 months surveyed. Moreover, virus abundance and diversity changed dynamically over time. Phylogenetic analysis revealed that the majority of viral sequences from East Lake, China displayed distinct clustering patterns compared with published sequences. These results supported the existence of a highly diverse and unique phytoplankton virus community in East Lake, China.